Born to Cry: A Genetic Dissection of Infant Vocalization - Ashbrook, David George; Roy, Snigdha; Clifford, Brittany G.; Riede, Tobias; Scattoni, Maria Luisa; Heck, Detlef H.; Lu, Lu; Williams, Robert W. (Frontiers in Behavioral Neuroscience, 2018)
Infant vocalizations are one of the most fundament and innate forms of behavior throughout avian and mammalian orders. They have a critical role in motivating parental care and through this contribute significantly to fitness and reproductive success. Dysregulation of these vocalizations has been reported to predict risk of central nervous system pathologies such as hypoxia, meningitis or autism spectrum disorder. Here we have used the expanded BXD family of mice, and a diallel cross between DBA/2J and C57BL/6J parental strains, to begin the process of genetically dissecting the numerous facets of infant vocalizations. We calculate heritability, estimate the role of parent-of-origin effects, and identify novel quantitative trait loci (QTLs) that control USVs on postnatal days 7, 8, and 9; a stage that closely matches human infants at birth. Heritability estimates for the number and frequency of calls are low, suggesting that these traits are under high selective pressure. In contrast, duration and amplitude of calls have higher heritabilities, indicating lower selection, or their importance for kin recognition. We find suggestive evidence that amplitude of infant calls is dependent on the maternal genotype, independent of shared genetic variants. Finally, we identify two loci on Chrs 2 and 14 influencing call frequency, and a third locus on Chr 8 influencing the amplitude of vocalizations. All three loci contain strong candidate genes that merit further analysis. Understanding the genetic control of infant vocalizations is not just important for understanding the evolution of parent-offspring interactions, but also in understanding the earliest innate behaviors, the development of parent-offspring relations, and the early identification of behavioral abnormalities. Keywords: Infant ultrasonic vocalizations; quantitative trait loci; heritability; parent-of-origin effects; crying; genetic dissection; BXD; USV